Great lakes, fragile seas [videorecording] - Seamans, Joe.; National Geographic Society (Washington, D.C.).; WQED (Television station : Pittsburg, Pa.). (Washington, D.C. The Society, 1991)
North America's freshwater seas have been subjected to decades of human abuse. Documents concurred groups attempting to repair past damage and confronting new threats to these waters. Shows how bodies of water affect lives of people. Shows the multifaceted aspects of the seas and other bodies of water. It discusses the beauty and magnificance of the bodies of waters as well as their harmful effects of man's abuse of our water resources.
VHS.
Keywords: Great Lakes -- Conservation of Environmental protection; Conservation of natural resources -- Citizen participation; Conservation of natural resources